Types of Insects in Organic and Semi-Organic Citrus Plantation - Misykat Sulthana Pora; Amin Setyo Leksono; Aminudin Afandhi (Indonesian Journal of Environment and Sustainable Development, 2016)
Using pesticide within semi-organic plantation system results in declining number and type of insects. Within the ecosystem, insect functions as herbivore, carnivore, detrivore and pollinator. The purpose of the study is to describe the structure and function of insect composition in organic and semi-organic orange plantation. The study used the blue and yellow trap pan method. The trap pan is installed one meter above the ground. 10 settlers are needed for 5 times of replication. The findings show that there are 1910 insects that belong to 5 orders and 24 families; formicidae family from hymenopetra is the most frequently found insect in the plantation. The Shannon Diversity Index showed difference between the organic and semi-organic plantation.The findings suggested that type of insects in the organic and semi-organic plantation is related to type of technology in each of the orange plantation.Keywords:  insect, organic, type